Zakat and waqf as financial sustainability tools among the womenpreneur in the B40 community: a qualitative observation of the Jarum Emas Project - Mohd Yusoff, Syarah Syahira; Adnan, Ieman Huda; Rosman, Romzie; Hassan, Rusni (Pusat Pungutan Zakat (PPZ-MAIWP), 2024)
This paper delves into the multifaceted challenges faced by mompreneurs in the B40 community and investigates the transformative potential of the Jarum Emas Project. Grounded in qualitative research methodologies, particularly the utilization of field notes, the study explores the intricate dynamics of financial constraints, health issues, and the lack of familial and community support experienced by these women. The Jarum Emas Project, framed within the principles of Islamic finance, relies on zakat and waqf to empower mompreneurs through various initiatives. The research unfolds by examining the experiences and observations meticulously recorded during the engagement with participants in sewing classes, workshops, and social gatherings. Field notes serve as a dynamic repository of the lived experiences of mompreneurs, capturing their resilience, challenges, and successes. Ethical considerations and reflexivity are intertwined with the research process, ensuring transparency, respect for participants, and an awareness of the researcher's own biases. The paper sheds light on how zakat and waqf, as Islamic financial instruments, can be harnessed to address financial constraints, provide sustainable infrastructure, and foster skill development. Moreover, it emphasizes the significance of community support and empowerment in the overall success of initiatives like the Jarum Emas Project. The findings contribute not only to the academic discourse on Islamic finance and community development but also provide practical insights for policymakers and practitioners seeking to empower marginalized women within underserved communities. The research advocates for a holistic and inclusive approach to mompreneur empowerment, blending financial support with skill development, community engagement, and ethical considerations.